2011
DOI: 10.1093/cercor/bhr130
|View full text |Cite
|
Sign up to set email alerts
|

Glial D-Serine Gates NMDA Receptors at Excitatory Synapses in Prefrontal Cortex

Abstract: N-methyl-D-aspartate receptors (NMDARs) subserve numerous neurophysiological and neuropathological processes in the cerebral cortex. Their activation requires the binding of glutamate and also of a coagonist. Whereas glycine and D-serine (D-ser) are candidates for such a role at central synapses, the nature of the coagonist in cerebral cortex remains unknown. We first show that the glycine-binding site of NMDARs is not saturated in acute slices preparations of medial prefrontal cortex (mPFC). Using enzymes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
144
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 84 publications
10
144
0
1
Order By: Relevance
“…Because activation of the NMDAR glycine-binding site by dserine is mandatory for the induction of synaptic plasticity [23][24][25][26][27][28][29], the LTP rescue observed in aged animals after supplementation with the co-agonist suggests that the gating managed by endogenous d-serine is altered with age. Accordingly, the age-related defect of pharmacologically isolated NMDAR-dependent synaptic potentials repetitively demonstrated in aged rodents [15,16,18,43] is reversed after saturating glycine-binding sites with d-serine or with the related agonist d-cycloserine [36][37][38][39].…”
Section: D-serine and Mechanisms Affecting D-serine-dependent Action mentioning
confidence: 99%
See 2 more Smart Citations
“…Because activation of the NMDAR glycine-binding site by dserine is mandatory for the induction of synaptic plasticity [23][24][25][26][27][28][29], the LTP rescue observed in aged animals after supplementation with the co-agonist suggests that the gating managed by endogenous d-serine is altered with age. Accordingly, the age-related defect of pharmacologically isolated NMDAR-dependent synaptic potentials repetitively demonstrated in aged rodents [15,16,18,43] is reversed after saturating glycine-binding sites with d-serine or with the related agonist d-cycloserine [36][37][38][39].…”
Section: D-serine and Mechanisms Affecting D-serine-dependent Action mentioning
confidence: 99%
“…Studies on age-related changes in synaptic availability of glutamate has led to negative results [22], arguing against the possibility of supplementation with the amino acid as a putative pharmacological strategy to prevent cognitive aging. Concerning the glycine-binding site, the recent use of pharmacological, enzymatic and/or gene invalidation strategies indicates that the amino acid d-serine, rather than glycine, is the main endogenous co-agonist of NMDAR in cerebral areas involved in memory processes [23][24][25][26][27]. In addition, it has been repetitively shown that d-serine is required for the expression of synaptic plasticity in neuronal networks of both CA1 and dentate gyrus hippocampal subfields [23][24][25][26][27][28][29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Selective DSR degradation by DAAO markedly reduces NMDAR neurotransmission in cortical and hippocampal preparations [22,47]. Moreover, DSR depletion in the medial prefrontal cerebral cortex diminishes NMDAR synaptic potentials and prevents LTP inhibition [48]. Recent data suggests that DSR release from astrocytes controls NMDAR-dependent plasticity and LTP in many thousands of excitatory synapses nearby [49], while in adulthood, neuronally-derived DSR regulates neuronal dendritic architecture in the somatosensory cortex [39].…”
Section: D-serine Neurobiology: An Overviewmentioning
confidence: 99%
“…In one example, a combination of CE with two-color fluorescence allowed the investigation of glycolipid catabolism in primary rat cerebella neurons with 500 ymol to 1 zmol sensitivity (Essaka et al, 2012). Laser-induced fluorescence (LIF) is the most sensitive detection technique used with CE (Pentoney and Sweedler, 1997); it can not only detect but quantify neurotransmitters in minute volumes of sample based on their retention time and area under the peak curve, and can be used to confirm analyte identity by spectral characteristics relative to known standards (Wise and Shear, 2006;Hatcher et al, 2008;Fossat et al, 2012). A dynamic range of nine orders of magnitude and 120 ymol sensitivity have been reported for glycosphingolipid metabolites (Dada et al, 2011).…”
Section: Detection Platforms Compatible With Microanalysismentioning
confidence: 99%